Public works for Poland? Active labour market policies during transition - Patrick A. Puhani; Viktor Steiner (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
Following the predominance of macroeconomic stabilisation policies and passive income support schemes in the first phase of transition, active labour market policies (ALMPs) have now come to play a more important role in transition economies. This paper looks at the Polish experience and provides empirical evidence on the effectiveness of ALMPs. We use the Polish Labour Force Survey of August 1994 in combination with its Supplement on the Evaluation of Labour Market Policies together with data on ALMP expenditure at the regional (voivodship) level. The macroeconometric analysis of the relationship between labour market flows and ALMP expenditure shows no significant effects. The microeconometric analysis reveals that ALMPs are not particularly well targeted at the problem groups in the labour market. That is, women and people with basic vocational education do not receive enough attention, whereas persons formerly employed in the public administration seem to have a privileged status in ALMPs. As to the effectiveness of ALMPs, the paper shows that former participants cannot expect to find employment more easily than their peers who have been unemployed but have not been in a programme. Subjective evaluations of former participants also suggest that ALMPs, but especially works programmes, have not increased their chances to find a job.
Keywords: E24; J64; J68; 330; unemployment; active labour market policies; Poland; Arbeitsmarktpolitik; Wirtschaftspolitische Wirkungsanalyse; Polen